Foucault and Latour: two outlines of social theory - Kazakov, Mstyslav (Filosofska Dumka, 2017)
The paper is dedicated to the study of actor-network theory of Bruno Latour and social theory of Michel Foucault. The research is based on the comparative analysis of both theories in the discourse of modern socio-humanitarian studies. The resemblance of both social theories, as well as historical succession of Latour’s theory (from Foucault’s) is noted. The author also constitutes principal “incompleteness”, the openness of Foucault’s and Latour’s projects to changes, and tries to demonstrate their advantage in comparison with other social theories. The fact of “openness” is seen as one of the advantages, as well as fundamentally different approach to research that is based on elimination of “metaobserving scientist” position and constitution of “the scientist who goes after the actors”. The author holds the position, according to which the practical use of the both theories may be productive in case of their synthesis (in which Latour’s ideas represent the conceptual crystallization of Foucault’s ideas, meanwhile, the ideas of Foucault can be seen as a sort of concretizing deployment of Latour’s general conceptual schemes). The demonstration of Foucault’s and Latour’s social theories “in action” is based on thought experiment which is related to the social theory, as well as to criminology. On the basis of modeled situation the author analyzes the approach to studying such situations in modern social theories that are based on ‘strict’ hierarchy, comparing this approach to the one, which is proposed by the actor-network theory and presented as ‘flexible’ approach.